Enhancing denitrification phosphorus removal with a novel nutrient removal process: Role of configuration - Liu, Hongbo; Zhu, Mengling; Gao, Saisai; Xia, Siqing; Sun, Liping (Chemical engineering journal (Lausanne, Switzerland : 1996), 2014)
•A novel tow configuration (process) was proposed to enrich DPB treating low strength real wastewater.•Configurational profiles of model intracellular compounds i.e. PHA and glycogen were characterized.•Configurational mass flow characteristics were demonstrated.•Two rules of thumb have been confirmed to enrich DPB with proper configuration. Role of configurations on enriching denitrifying phosphorus removing bacteria (DPB) by biological nutrient removal processes was discussed. Effects of configurations on enhancement of denitrifying phosphorus removal in a novel nutrient removal process, the STB (six-tank-bioreactor) process were investigated. Profiles of model intracellular compounds i.e. glycogen and PHA (poly-hydroxyalknoates) under different configurations were characterized in order to reveal the biochemical pathway that DPBs might follow in the STB process. Mass flow characteristics of main pollutants under different configurations were also illustrated. Results showed that a higher anoxic to total volume ratio and the multi-barrier bioreactor strategy were crucial factors to enhance denitrifying phosphorus removal in the STB process. Both of the configurations performed well with average removal efficiencies of 74%, 98%, 51% and 85% under configuration I, and 74%, 99%, 72% and 70% under configuration II for COD, NH3–N, TN and TP respectively. A higher denitrifying phosphorus removal efficiency was achieved under configuration II than configuration I due to a bigger anoxic to total volume ratio.